2019
DOI: 10.1101/705129
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Leveraging Gene Co-expression Patterns to Infer Trait-Relevant Tissues in Genome-wide Association Studies

Abstract: AbstractGenome-wide association studies (GWASs) have identified many SNPs associated with various common diseases. Understanding the biological functions of these identified SNP associations requires identifying disease/trait relevant tissues or cell types. Here, we develop a network method, CoCoNet, to facilitate the identification of trait-relevant tissues or cell types. Different from existing approaches, CoCoNet incorporates tissue-specific gene co-expression networks const… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 69 publications
0
10
0
Order By: Relevance
“…We employed MIGWAS [ 7 ], CoCoNet [ 9 ], and ANNOVAR [ 10 ] software packages to infer trait-relevant tissues based on next-generation sequencing omics data (e.g. GTEx data [ 16 ]) and annotated the variants obtained from GWAS and harbored by miRNAs targeted genes associated with traits.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…We employed MIGWAS [ 7 ], CoCoNet [ 9 ], and ANNOVAR [ 10 ] software packages to infer trait-relevant tissues based on next-generation sequencing omics data (e.g. GTEx data [ 16 ]) and annotated the variants obtained from GWAS and harbored by miRNAs targeted genes associated with traits.…”
Section: Methodsmentioning
confidence: 99%
“…Composite likelihood-based Covariance regression Network model (CoConet) is a network method for identification of trait-relevant tissues or cell types by incorporating tissue-specific gene co-expression networks [ 9 ]. CoCoNet further understands data from GWAS by demonstrating gene co-expression sub-networks which helps predict gene-level association effect sizes on and GWAS traits and diseases.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, we intersected the SNVs participating in scReQTLs with SNVs significantly associated with phenotypes by GWAS [38]. This analysis showed that 18 (out of the 408 unique scReQTL SNVs, 4.4%) were present in GWAS; these 18 SNVs participated in 84 scReQTL correlations (Supplementary Table 5).…”
Section: Screqtls and Gwasmentioning
confidence: 99%
“…Third, the potential mediators in genomics are often correlated with each other, sometimes quite strongly. For example, methylation measurements on proximal CpG sites are generally similar to each other and genes in the same pathway also show coordinated co-expression pattern [110] . However, existing univariate and multivariate mediation methods do not explicitly model correlation among potential mediators.…”
Section: Introductionmentioning
confidence: 98%